Analysis of adverse events with lumen apposing metal stents for drainage of pancreatic fluid collections - Pawa, Rishi; Dorrell, Robert; Nguyen, Madison; Russell, Greg; Gilliam, John (Endoscopy International Open, 2023)
Background and study aims Innovations in endoscopic management of pancreatic fluid collections (PFCs) using lumen apposing metal stents (LAMS) have rendered it a preferred approach for drainage of PFCs. These advances have not come without concern for adverse events (AEs). We present our experience with LAMS for drainage of PFCs and analyze factors that contribute to LAMS-related AEs.Patients and methods From November 2015 to October 2021, a retrospective analysis was performed of patients undergoing endoscopic management of PFCs using LAMS. All AEs were classified as either early (<48 hours) or late (>48 hours). Univariate and multivariate analysis were performed using logistic regression to assess the relationship between independent variables and AEs.Results A total of 119 patients with symptomatic PFCs underwent endoscopic drainage with LAMS. There were 16 AEs (12.4%). These included systemic inflammatory response syndrome (SIRS) (n=2), stent occlusion (n=5), bleeding (n=7), and stent migration (n=2). Univariate analysis of risk of AEs showed that no variables approached statistical significance. Of the seven patients who developed bleeding, five had pseudoaneurysms following LAMS placement and underwent angioembolization by an interventional radiologist. The average time to bleeding was 9.3 days (standard deviation 7.3) with all bleeding events occurring within 3 weeks. In a multivariate model, pseudocysts and presence of paracolic gutter extension were associated with an increased risk of bleeding.Conclusions Endoscopists should be aware of the risk factors for LAMS-related bleeding and tailor their drainage strategy, including utilization of plastic stents for drainage of pseudocysts and adherence to a strict imaging interval and follow-up protocol.
Keywords: Pancreas; Endoscopic ultrasonography; Intervention EUS; Quality and logistical aspects; GI radiology